PERENCANAAN ALOKASI DANA KAMPUNG (ADK) KABUPATEN MAMBERAMO RAYA (KAJIAN PADA BPMPK DAN BPKAD) - Marvine Wutoy (Universitas Cenderawasih, 2020)
This article examines the process in the planning stages of the Village Fund Allocation (ADK) as well as the factors inhibiting and supporting ADK in Mamberamo Raya district. This research uses a qualitative approach with descriptive analysis. Observation data through observation, documentation and in-depth interviews with information consisting of the Head of BPMPK, the Head of BPKAD, the Head of the Legal Department and the P3MD Expert. The results of the research on the Village Fund Allocation Planning by the Community Empowerment Agency and the Village Government found several factors that became obstacles and supporters, inhibiting factors, among others, difficulties in the lack of understanding of officials about their duties and functions to help difficult coordination due to lack of cooperation and also difficult communication. be careful with the principles of intergovernmental fund transfers in ADK planning according to Law Number 6 of 2014 concerning Villages